If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + -6(x + -2) = -2 Reorder the terms: 40 + -6(-2 + x) = -2 40 + (-2 * -6 + x * -6) = -2 40 + (12 + -6x) = -2 Combine like terms: 40 + 12 = 52 52 + -6x = -2 Solving 52 + -6x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-52' to each side of the equation. 52 + -52 + -6x = -2 + -52 Combine like terms: 52 + -52 = 0 0 + -6x = -2 + -52 -6x = -2 + -52 Combine like terms: -2 + -52 = -54 -6x = -54 Divide each side by '-6'. x = 9 Simplifying x = 9
| 8x+6(-2x+5)=2x-18 | | .66x-1.66=.5x+.83 | | 10x+12-5x+6=-12 | | 4c+23=2+5b | | 4x-15=-95 | | 5n-16-8n=19 | | 26.02*2.006= | | -10x^2+285+650=0 | | 68=2l+(12+2w) | | 3(k+8)+3=2k-7 | | 0.3*0.9= | | 5(x+2)+3=6(3x+9)-2 | | 5Xv-18-4=-36 | | 1/2k-3=-9x-4 | | 4/5=10/3x | | 3/4x-2/3=7/12 | | 3x^2-42x+135=0 | | 4/5=10/3 | | 1-9/5x3 | | -8g+10=-10-12g | | x+-4=-15 | | X=4(1)+8 | | p-25/140=12/42 | | 15/16x=11 | | 4x^2(x^2+6xy-7y^2)=x | | .6(x+8)-.8(5x+2)=10 | | 3/7/6 | | 2x+2(3x+4)=8+8x | | -4x^2+3=-6 | | 12=-r+11 | | (6x+7)-29=6x | | -3(2x+1)+x=2-(4x-2) |